1994
DOI: 10.1007/bf02536628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n−3 and n−6 fatty acids on the activities and expression of hepatic antioxidant enzymes in autoimmune‐prone NZB×NZW F1 mice

Abstract: Menhaden fish oil (FO) containing n-3 fatty acids dramatically extends the life span and delays the onset and progression of autoimmune disease in (NZBxNZW)F1 (B/W) female mice as compared to those fed corn oil (CO) rich in n-6 lipids. As an inefficient antioxidant defense system has been linked to autoimmune diseases, the present study was undertaken to determine whether the protective action of n-3 lipids is mediated through their antioxidant defense system. Weanling B/W mice were fed a nutritionally adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 60 publications
4
78
2
Order By: Relevance
“…A 10-min centrifugation at 2000 g replaced the lengthy organic solvent extraction of pigments [13]. Malondialdehyde (as tetraethyl acetal; Aldrich Chemical Co., Milwaukee, WI) was used as a standard.…”
Section: Measurement Of Tbarsmentioning
confidence: 99%
“…A 10-min centrifugation at 2000 g replaced the lengthy organic solvent extraction of pigments [13]. Malondialdehyde (as tetraethyl acetal; Aldrich Chemical Co., Milwaukee, WI) was used as a standard.…”
Section: Measurement Of Tbarsmentioning
confidence: 99%
“…In both liver and spleen, we found that fish oil feeding suppressed expression of message for these enzymes (61,64). In the liver, antioxidant enzyme activity was determined, and also found to be higher in fish oil fed animals.…”
Section: Fish Oil Fats and Autoimmune Disease In The Short-lived B/w mentioning
confidence: 74%
“…Mice on both FO and CO gained the same amount of weight (40-45 g). Northern blot analysis of kidney extracts from 6-month-old FO-fed mice revealed no detectable levels of IL-10, IL-6, and TNF-a mRNA, whereas these cytokine mRNA were easily detected in 6-month-old CO-fed mice (Chandrasekar & Fernandes, 1994). In contrast to the cytokine mRNA, FO-fed mice showed higher renal levels of the antioxidant enzymes catalase (EC 1.1 1.1.6), glutathione peroxidase (EC 1.1 1.1.9), and superoxide dismutase (EC 1.15.…”
Section: Role(s) Of N-3 and N-6 Fatty Acids On Gene Expression In Autmentioning
confidence: 89%
“…Furthermore, significantly lower estimated peroxidation indices and generation of thiobarbituric acidreactive substances were noted in FO-fed mice. These findings suggest that one of the mechanisms by which the n-3 lipids may delay the onset of autoimmune disease could be through the maintenance of higher hepatic antioxidant enzyme expression and activity levels (Venkatraman et al 1994).…”
Section: Role(s) Of N-3 and N-6 Fatty Acids On Gene Expression In Autmentioning
confidence: 93%
See 1 more Smart Citation